Intramuscular levothyroxine: a solution to a mental health related thyroid crisis. Issue 8 (20th August 2019) - Laycock, Kate; Beale, Chloe; Peters, Catherine; Anderson, John
Abstract : A 53-year-old woman was admitted with thyroid storm and severe behavioural problems. She had longstanding bipolar affective disorder. She was psychotic and obstructed in-patient medical management for thyroid storm. She required one-to-one psychiatric nursing and was placed under section 3 of the Mental Health Act meaning she could be detained in hospital for psychiatric treatment for up to 6 months. She underwent a total thyroidectomy. Due to her paranoid mental state, she refused treatment and the administration of thyroid hormone replacement was difficult. Postoperatively, intramuscular levothyroxine was used effectively to stabilise her thyroid function. There are no consensus guidelines on the use of parenteral levothyroxine and intramuscular levothyroxine is rarely used. This case uniquely illustrates its utility with bi-weekly blood tests showing a fast and stable response to intramuscular hormone replacement.